Welsh‐language prestige in adolescents: attitudes in the heartlands. (4th December 2019) - Price, Abigail Ruth; Tamburelli, Marco
Abstract : We investigate covert attitudes towards Welsh and English as a medium of informal communication among L1 Welsh‐English bilingual adolescents. We collected quantitative data using an adaptation of the Matched‐Guise technique, testing measures of social attractiveness within youth culture via an indirect method. A total of thirty‐five adolescents took part in this study. We perform a 2 (language: Welsh /English) × 2 (register: high/low) × 2 (participant gender: male/female) mixed‐design ANOVA, with participant gender as the between‐subjects variable. Results show English rated more favourably than Welsh overall, with female participants rating Welsh guises significantly more highly than males. This lends empirical support to the perception of Welsh as a language of school and officialdom while English fulfils the language of leisure. Abstract : Investigamos actitudes encubiertas hacia el galés y el inglés como medio de comunicación informal entre adolescentes bilingües L1 de galés e inglés. Recopilamos datos cuantitativos usando una adaptación de la técnica Matched‐Guise, analizando medidas de atractivo social en la cultura juvenil a través de un método indirecto. En el estudio participaron un total de treinta y cinco adolescentes. Llevamos a cabo un diseño ANOVA mixto 2 (idioma: galés/inglés) x 2 (registro: alto/bajo) x 2 (género del participante: masculino/femenino), con el género del participante como la variable entre sujetos. Los resultados muestran que en general el inglés tiene una valoración más alta que el galés, y que las participantes femeninas valoran de manera significativamente más alta lasformas galesas que los masculinos. Esto proporciona apoyo empírico a la percepción del galés como el idioma de la escuela y del funcionariado mientras que el inglés ocupa el lugar del idioma del ocio.